Scalar politics, language ideologies, and the sociolinguistics of globalization among transnational Korean professionals in Hong Kong. (June 2016) - Bailey, Adrian J.; Canagarajah, Suresh; Lan, Shanshan; Powers, Devereux Gong
Abstract : This paper argues that the sociolinguistics of globalization is accompanied by a constitutive scalar politics. Based on ten interviews with Korean professionals in Hong Kong, we report that Korean migrants' use and experience of English is characterized by competing language ideologies we identify as: Pragmatic English/Perfect English, Multilingualism/English Only, and Global Language/Local Language. Tensions within these ideologies were revealed as respondents referenced the contexts of their daily lives as intersecting sets of geographic, temporal, and social scales. We discuss how sociolinguistic relations associated with the transnational lifecourse, hybridizing identity, and racialization were imagined in ways that re‐negotiated these scales to serve the interests of the participants and provide coherence to their communicative practices. Sociolinguistic relations both reference scales and constitute them. We conclude that attending to scales and scalar politics provides a better explanatory framework for the ways the uneven linguistics markets of globalization are negotiated by transnational subjects.